SAMRATED: A Conceptual Integration of SAMR and SDT to Evaluate Digital Transformation in Higher Education Learning - Ajeng Ayu Milanti; Cahaya Juniarti; Hilman Gufron (Universitas Pendidikan Ganesha, 2026)
The integration of digital technology in higher education continues to expand; however, its implementation is often limited to the digitization of learning materials, resulting in suboptimal improvements in students’ motivation and learning outcomes. This study aims to analyze the effectiveness of e-module utilization in enhancing students’ learning outcomes and intrinsic motivation through the integration of the Substitution, Augmentation, Modification, Redefinition (SAMR) framework and Self-Determination Theory (SDT). A mixed-methods approach with a quasi-experimental design was employed, involving 247 undergraduate students divided into an experimental group (e-module) and a control group (e-book). Data were collected through learning achievement tests, SAMR–SDT-based motivation questionnaires, and classroom observations, and were analyzed using nonparametric statistical tests and Partial Least Squares Structural Equation Modeling (PLS-SEM). The results revealed that students who used the e-module demonstrated greater improvements in learning outcomes than those who used the e-book. Structural model analysis further indicated that the redefinition dimension was the most influential factor in supporting students’ autonomy, competence, and relatedness, which subsequently contributed to intrinsic motivation. This study concludes that the integration of SAMR and SDT through the SAMRATED framework has the potential to serve as an effective approach for evaluating and designing more transformative digital learning environments. The findings imply that e-module development should prioritize collaborative and meaningful learning activities that fulfill students’ psychological needs in order to enhance the quality of learning in higher education.